2022
DOI: 10.1007/s11064-022-03761-3
|View full text |Cite
|
Sign up to set email alerts
|

Mahonia Alkaloids (MA) Ameliorate Depression Induced Gap Junction Dysfunction by miR-205/Cx43 Axis

Abstract: Depression has become an important disease threatening human health. In recent years, the e cacy of Traditional Chinese Medicine (TCM) in treating the disease has become increasingly prominent, so it is meaningful to nd new antidepressant TCM. Mahonia fortune (Lindl.) Fedde is a primary drug in traditional formulas for the treatment of depression, however, the exact mechanism of its action is unclear. This study aimed to research the effect of MA on the improvement of gap junction function in depression via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Motion inhibition test (MIT) was as described previously. 33 , 34 In short, the animal was placed in the center of a circular whiteboard 40 cm in diameter and observed for 30s, and the time the animal left the circular whiteboard was recorded. The experiment simulated a state of reduced movement in depressed animals.…”
Section: Methodsmentioning
confidence: 99%
“…Motion inhibition test (MIT) was as described previously. 33 , 34 In short, the animal was placed in the center of a circular whiteboard 40 cm in diameter and observed for 30s, and the time the animal left the circular whiteboard was recorded. The experiment simulated a state of reduced movement in depressed animals.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that inhibition of connexin 43 exacerbates depressionlike behavior [180]. Supporting these findings, further research has indicated that the gap junction channels of astrocytes could potentially serve as targets for new antidepressant drug development [181,182]. Approaches such as enhancing astrocytic lactate production or promoting lactate uptake by neurons could potentially restore energy balance, improve sleep quality, and ameliorate comorbid conditions.…”
Section: Astrocyte-neuron Lactate Shuttlementioning
confidence: 96%
“…In a study using an unpredictable chronic mild stress (UCMS)-induced mouse model of depression, miR-221/222 directly bound to the 3′ untranslated regions (3′ UTR) of Cx43 mRNA and downregulated Cx43 protein levels; this could be reversed by genistein treatment, subsequently ameliorating depression-like behaviors in the mice [ 21 ]. miR-205 also targeted the Gja1 gene, which encodes the Cx43 protein [ 22 ]. The administration of Mahonia alkaloids reduced miR-205 content and consequently improved Cx43 levels, alleviating depression in reserpine-treated rats [ 22 ].…”
Section: Disorders Modulated By Noncoding Rnas Through Relevant Conne...mentioning
confidence: 99%
“…miR-205 also targeted the Gja1 gene, which encodes the Cx43 protein [ 22 ]. The administration of Mahonia alkaloids reduced miR-205 content and consequently improved Cx43 levels, alleviating depression in reserpine-treated rats [ 22 ]. miR-106a was confirmed to bind to the 3′ UTR of Cx43 mRNA, and an miR-106a antagonist could repress apoptosis, alleviate oxidative stress, and enhance Cx43 protein content in glucose oxidase-treated rat cochlear marginal cells [ 23 ].…”
Section: Disorders Modulated By Noncoding Rnas Through Relevant Conne...mentioning
confidence: 99%
See 1 more Smart Citation